Temperature-insensitive curvature sensor based on anti-resonant reflection guidance and Mach–Zehnder interferometer hybrid mechanism. (12th September 2019) - Wang, Shuang; Shan, Chenxi; Jiang, Junfeng; Liu, Kun; Zhang, Xiaofei; Han, Qun; Lei, Jincheng; Xiao, Hai; Liu, Tiegen
Abstract: A temperature-insensitive optical fiber curvature sensor based on hollow-core fiber is proposed. The hybrid guidance mechanism is a combination of anti-resonant reflecting guidance and the Mach–Zehnder interferometer. The curvature can be detected through the wavelength interval between the two kinds of lossy dips resulting from the two above-mentioned guidance mechanisms. The curvature sensitivity is −0.54 nm/m −1 and −2.02 nm/m −1 in the curvature range of [0 m −1, 7.04 m −1 ] and [7.04 m −1, 11.87 m −1 ], respectively. And the temperature cross-sensitivity of the sensor is only 5.54 pm °C −1, which makes the device attractive for potential applications in curvature measurements.